2014
DOI: 10.1103/physrevb.90.245117
|View full text |Cite
|
Sign up to set email alerts
|

Unquenchedeg1orbital moment in the Mott-insulating antiferromagnetKOsO4

Abstract: Applying the correlated electronic structure method based on density functional theory plus Hubbard U interaction, we have investigated the tetragonal scheelite structure Mott insulator KOsO4, whose e 1 g configuration should be affected little by spin-orbit couping (SOC). The method reproduces the observed antiferromagnetic Mott insulating state, populating the Os d z 2 majority orbital. The quarter-filled eg manifold is characterized by a symmetry breaking due to the tetragonal structure, and the Os ion show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…It is unsurprising that the two magnetic interactions would be comparable in strength due to their relative superexchange pathways. In comparison, materials such as KRuO 4 [64] and KOsO 4 [65,66] share the same I4 1 /amd magnetic sublattice comprised of Ru and Os ions, but break the oxygenbased superexchange connection along J 2 . In these systems, magnetic order resides in the J 2 = 0 limit of the Heisenberg J 1 -J 2 model, where moments order within a Neél antiferromagnetic state and an unfrustrated J 1 [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…It is unsurprising that the two magnetic interactions would be comparable in strength due to their relative superexchange pathways. In comparison, materials such as KRuO 4 [64] and KOsO 4 [65,66] share the same I4 1 /amd magnetic sublattice comprised of Ru and Os ions, but break the oxygenbased superexchange connection along J 2 . In these systems, magnetic order resides in the J 2 = 0 limit of the Heisenberg J 1 -J 2 model, where moments order within a Neél antiferromagnetic state and an unfrustrated J 1 [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…High valent osmates can have an open e g shell rather than t 2g shell. Song et al 13 have reported a theoretical study 13 of KOsO 4 with heptavalent Os, where large SOC, strong correlations, and structural symmetry breaking conspire to produce an unexpectedly large orbital moment in the e 1 g shell that nominally supports no orbital moment. The moment arises due to distortion from ideal tetrahedral symmetry of the ion, which allows mixing in of orbitals that support an orbital moment.…”
Section: Introductionmentioning
confidence: 99%
“…This becomes relevant when the ratio λ/∆ c is not negligibly small (λ is the coupling constant of the atomic SOC). In fact, a relatively large value of λ/∆ c ∼ 0.18 was reported for KOsO 4 from the firstprinciples calculation 37 . When we take into account such a SOC effect in the second-order perturbation, the e g and t 2g levels are further split: the e g levels are lowered while keeping the fourfold degeneracy, whereas the t 2g levels are split into twofold and fourfold [see the rightmost panel in Fig.…”
Section: A Effective Two-orbital Hamiltonianmentioning
confidence: 92%